Ambulatory measurement of 3D knee joint angle - Favrea, J.; Jolles, B. M.; Aissaoui, R.; Aminian, K. (Journal of Biomechanics, 2008)
Three-dimensional measurement of joint motion is a promising tool for clinical evaluation and therapeutic treatment comparisons. Although many devices exist for joints kinematics assessment, there is a need for a system that could be used in routine practice. Such a system should be accurate, ambulatory, and easy to use. The combination of gyroscopes and accelerometers (i.e., inertial measurement unit) has proven to be suitable for unrestrained measurement of orientation during a short period of time (i.e., few minutes). However, due to their inability to detect horizontal reference, inertial-based systems generally fail to measure differential orientation, a prerequisite for computing the three-dimentional knee joint angle recommended by the Internal Society of Biomechanics (ISB). A simple method based on a leg movement is proposed here to align two inertial measurement units fixed on the thigh and shank segments. Based on the combination of the former alignment and a fusion algorithm, the three-dimensional knee joint angle is measured and compared with a magnetic motion capture system during walking. The proposed system is suitable to measure the absolute knee flexion/extension and abduction/adduction angles with mean (SD) offset errors of -1° (1°) and 0° (0.6°) and mean (SD) root mean square (RMS) errors of 1.5° (0.4°) and 1.7° (0.5°). The system is also suitable for the relative measurement of knee internal/external rotation (mean (SD) offset error of 3.4° (2.7°)) with a mean (SD) RMS error of 1.6° (0.5°). The method described in this paper can be easily adapted in order to measure other joint angular displacements such as elbow or ankle.